Peran Koperasi Terhadap Kesejahteraan Ekonomi Masyarakat di Desa Air Kelik - Aprilia, Sindi (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2024)
This research aims to understand the role of the Aik Nyato Lestari Cooperative in enhancing the economic welfare of the Air Kelik Village community, East Belitung Regency. Indonesia, as an agrarian country, has many villages that rely on the agricultural sector and small enterprises. Air Kelik Village faces challenges in access to capital, technology, and markets, making cooperatives a potential solution. Through cooperative management socialization conducted by the KKN team group 15 IAIN SAS BABEL, it is hoped that the community's understanding of cooperatives can be improved. The Aik Nyato Lestari Cooperative, with a vision to create an advanced, prosperous, and independent community economy, has various work programs to support its members. This research uses qualitative methods through interviews and focus group discussions. The results show that the cooperative plays an important role in procuring raw materials, marketing products, and increasing member income, although there are still financial management issues that need to be addressed. Additionally, this cooperative also promotes environmental sustainability through more eco-friendly farming practices. The implementation of skill training programs for cooperative members has also proven to enhance both individual and collective capacities in managing businesses more efficiently. In conclusion, the Aik Nyato Lestari Cooperative has a significant contribution in improving the economic and social welfare of the Air Kelik Village community, although further development is needed in managerial and operational aspects.